Comparison of Lead Removal by Various Types of Swine Bone Adsorbents - Sudaratn Lurtwitayapont (EnvironmentAsia, 2010)
The removal capacities of lead by bone adsorbents, prepared in various appropriate types, have been studied in a single component system using agitated batch sorption. The adsorbent characteristics before and after sorption were examined by electron microscopy, surface area analysis (BET), crystalline structure by x-ray diffractometer (XRD), chemical compositions by x-ray fluorescence (XRF) and by Fourier transform infrared (FT-IR). The results showed that the main component of swine bone adsorbents is calcium hydroxyl¬apatite with Ca/P ratio is 1.70; the calcium ion and the range of mesopores of the appropriate pore sizes are the important factors for the ion-exchange process and the sorption process. The effects of carbonization, activation, initial metal ion solution concentration, contact time and quantities of bone adsorbent mass were studied. The capacity removal of lead onto bone powder, bone char and activated bone char were 417, 1828 and 690 mg/g, respectively, for 10 mg/L and pH 5±0.1 of the initial lead ion solution concentration, with an agitation speed 175 rpm. The sorption isotherm was also studied and indicated that the Langmuir isotherm model closely fits the sorbtion of lead onto bone char.